Decolonizing English Language Teaching: Integrating Indian Cultural Traditions through Digital Platforms - Arya Asok (Digital Crossroads: Integrating Humanities, Science and Technology Edition 1, 2025)
There is an urgent need to bridge digital innovation with cultural preservation and inclusive pedagogical approaches and this intersection offers an opportunity to reimagine traditional learning methods. Drawing on post-method pedagogy, and the need for decolonization, this paper analyses the role of online platforms like Natyasutra in decolonizing English language learning through digital narratives and online classes showcasing Indian art and culture. Natyasutra is an online platform that attempts to preserve Indian classical art forms digitally. The Great Indian Stories is one of the programs in Natyasutra, choreographed and presented by Bharatanatyam dancer and musician Rajasree Warrier. It utilizes dance techniques to enact Panchatantra and Jataka tales. These stories are retold through dance mudras coupled with narration in English. This learning experience revitalizes the oral tradition of storytelling. The long-lost significance of Panchatantra and Jataka tales is revived with the help of technology. Thereby, learners receive a visual representation of the stories. This type of learning is visual and kinesthetic, hence fostering stress-free learning. Learners also get exposed to Indian culture, traditions, and art forms. This type of Language learning enables the decolonization of English language learning by incorporating traditional pedagogies. Subsequently, digital platforms like Natyasutra can be incorporated into ESL classrooms to enhance the learning experience. While the study focuses specifically on the Indian educational context and classical art forms, its findings have broader implications for other post-colonial societies seeking to integrate indigenous knowledge systems into language education.